Village Stratification for Policy Analysis: Multiple Development Domains in the Ethiopian Highlands of Tigray - Kruseman, Gideon; Ruben, Ruerd; Tesfay, Girmay (International Food Policy Research Institute, 2006)
Many countries in Sub-Saharan Africa suffer from problems related to poverty, natural resource degradation, and the complex interactions between these phenomena (Cleaver and Schreiber 1994). In the northern Ethiopian highlands of Tigray region, problems of poverty and degradation are extremely severe: population density is very high, rainfall is scarce and erratic, and soil fertility is low. Under such conditions, farmers need to rely on external inputs and soil conservation practices in order to stabilize or increase yields. Within the current land use pattern, a wide range of different options are available for intensification of production systems. The selection of appropriate pathways for intensification may be different for specific locations. Therefore, village stratification can be used to select technologies and practices that are applied under particular agro-ecological, socioeconomic, and institutional conditions.